2016
DOI: 10.1037/neu0000223
|View full text |Cite
|
Sign up to set email alerts
|

Late-life depression is not associated with dementia-related pathology.

Abstract: Objective To test the hypothesis that late-life depression is associated with dementia related pathology. Method Older participants (n=1,965) in 3 longitudinal clinical-pathologic cohort studies who had no cognitive impairment at baseline underwent annual clinical evaluations for a mean of 8.0 years (SD = 5.0). We defined depression diagnostically, as major depression during the study period, and psychometrically, as elevated depressive symptoms during the study period, and established their relation to cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 63 publications
3
44
1
2
Order By: Relevance
“…17 Whether depression shares common pathologic mechanisms with AD-related pathology remains controversial. 18,19 On the other hand, a large body of imaging research has demonstrated the vascular and neural bases for these disorders. While OSA is known for its destructive nature in the cerebral vascular and neural systems, whether OSA plays an important role in the cognitive deteriorating process in older adults with amnestic MCI (aMCI) and depression is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…17 Whether depression shares common pathologic mechanisms with AD-related pathology remains controversial. 18,19 On the other hand, a large body of imaging research has demonstrated the vascular and neural bases for these disorders. While OSA is known for its destructive nature in the cerebral vascular and neural systems, whether OSA plays an important role in the cognitive deteriorating process in older adults with amnestic MCI (aMCI) and depression is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Late-life depression is associated with an increased risk for dementia with an odds ratio of 1.85 according to meta-analyses of 23 prospective studies including more than 49,600 participants (1,2). Notably, depression has been shown to be associated with faster decline of cognitive performance and with the clinical diagnosis of dementia but not with the traditional dementia pathologies such as beta-amyloid plaques, tau tangles, Lewy bodies, hippocampal sclerosis, microinfarcts, and macroinfarcts (3)(4)(5)(6). How depression and its associated molecular changes act to increase dementia risk is not well understood and is the focus of this work.…”
mentioning
confidence: 99%
“…Multiple studies have demonstrated an association between neuropsychiatric symptoms and an increased risk of dementia and AD (4144), although the mechanisms underlying this association remain unclear. While some studies have suggested that depression is associated with an increase in accumulation of brain amyloid, neurofibrillary tangles, or hippocampal atrophy (4547), others have shown no association between dementia-related markers of pathology and depression (48). Anxiety has also been linked to increased levels of plaques and tangles (46).…”
Section: Outcome Measures For Prevention Trialsmentioning
confidence: 99%